1973
DOI: 10.2466/pr0.1973.33.3.967
|View full text |Cite
|
Sign up to set email alerts
|

Internal-External Control and Ideology

Abstract: It was hypothesized that internal Ss would agree more with ideologies which emphasize the importance of self-determination of behavior, whereas external Ss would agree more with ideologies which emphasize the importance of social determination of behavior. Internals scored significantly higher on the traditional American ideology scale, whereas externals scored significantly higher on the New Left scale and one assessing a political philosophy of conservatism. These significant results ( p < .02) for colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Rotter (1975) warned clinicians to not assume that individuals with an internal LOC will possess only positive traits. Despite that caution, according to researchers Fink and Hjelle (1973) internal LOC indeed became exalted since it reflected the Western cultural ideals of personal autonomy and industriousness. As a result, some experts came to view the research on LOC as biased by the assumption that an internal LOC is more functional than an external LOC (Fink & Hjelle, 1973).…”
Section: Sociocultural Factors and Locmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotter (1975) warned clinicians to not assume that individuals with an internal LOC will possess only positive traits. Despite that caution, according to researchers Fink and Hjelle (1973) internal LOC indeed became exalted since it reflected the Western cultural ideals of personal autonomy and industriousness. As a result, some experts came to view the research on LOC as biased by the assumption that an internal LOC is more functional than an external LOC (Fink & Hjelle, 1973).…”
Section: Sociocultural Factors and Locmentioning
confidence: 99%
“…Despite that caution, according to researchers Fink and Hjelle (1973) internal LOC indeed became exalted since it reflected the Western cultural ideals of personal autonomy and industriousness. As a result, some experts came to view the research on LOC as biased by the assumption that an internal LOC is more functional than an external LOC (Fink & Hjelle, 1973). The LOC research, culturally biased though it may be, has shown that internal LOC is associated not only with better mental health but also with better job performance and life satisfaction (Marks, 1998).…”
Section: Sociocultural Factors and Locmentioning
confidence: 99%
“…It is an ethic of individual effort and has little if anything to say about external, structural impediments to achievement" (Sampson, 1983, p. 135). Indeed, researchers have shown internality to be related to the Protestant ethic and traditional American values (Fink & Hjelle, 1973;Mirels & Garrett, 1971;Rotter, 1975). This bias is resounded in Lefcourt's (1982) assertion, "Man must come to be more effective and more able to perceive himself as the determiner of his fate if he is to live comfortably with himself" (p. 3).…”
Section: Sociocultural Influences On Locus Of Controlmentioning
confidence: 99%
“…Consequently, Thomas (1970) could argue that the leftist flavor of the external alternatives led to a spurious correlation of activism with externality. Alternatively, Fink and Hjelle (1973) argued that externals are attracted to ideologies that emphasize the importance of societal determination of behavior, whereas internals prefer ideologies emphasizing self-determination. Because campus activist groups generally held left-wing views that emphasize societal determination, externals would be attracted to them.…”
Section: Sociopolitical Behaviormentioning
confidence: 99%